Development of a Textbook on Tai Yao Local Language and Culture for Kutchik Wittayakarn School, Kalasin Province - Puribhaddasiri (Loeknok), Phrakittiwirot; Sribunrueang, Pacharakit; Khraiboot, Adcharaporn (Journal of Buddhist Education and Research (JBER), 2026)
This research aimed to: 1) study and collect information concerning the Tai Yao language and local culture of Ban Kut Chik, Tha Khantho District, Kalasin Province; and 2) develop a textbook on Tai Yao language and local culture for Kutchik Wittayakarn School, Kalasin Province. The target groups consisted of five local wisdom experts and seven specialists. The research instruments included an interview form on Tai Yao language and local culture, a textbook on Tai Yao language and local culture, and an evaluation form assessing the appropriateness, feasibility, and usefulness of the developed textbook. Data were analyzed using mean and standard deviation. The findings revealed that the collected information covered three major areas: 1) the historical background of the Tai Yao people in Kut Chik Subdistrict, including local legends and the significant role of Thao Khun Chiang Pattha as a community leader and cultural scholar; 2) fundamental knowledge of the Tai Yao language, highlighting its distinctive vowel sound /ɤː/, its recognition as a National Intangible Cultural Heritage in 2014, and its linguistic characteristics, including 19 consonant sounds, 18 monophthongs, 3 diphthongs, 4 tones, and 6 consonant clusters; and 3) fundamental knowledge of Tai Yao culture, particularly the traditional customs known as “Heet Sip Song Kong Sip Si” (Twelve Traditions and Fourteen Practices), which have been transmitted through generations. The evaluation of the developed textbook indicated an overall high level of appropriateness, feasibility, and usefulness (x̄ = 3.92). When considered by aspect, usefulness received the highest mean score (x̄ = 4.02), followed by appropriateness (x̄ = 3.88) and feasibility (x̄ = 3.85). The findings suggest that the developed textbook is suitable for preserving and promoting Tai Yao language and cultural heritage within educational settings.